Restraining effect of aggregates on autogenous shrinkage in cement mortar and concrete. (28th June 2021) - Lu, Tianshi; Li, Zhenming; Huang, Hao
Highlights: The autogenous shrinkage of CEM I and CEM III/B mortar and concrete is studied by experiments and simulation. The activation energy concept is adopted to simulate the time-dependent behavior of cement paste, i.e. creep. The Pickett's model is extended to consider the effect of creep on the restraining effect of aggregates. Abstract: Shrinkage-induced cracking can impair the durability of concrete structures. In the past few decades, this topic has drawn more and more attention. Shrinkage of mortar and concrete is actually the result of the interaction between the shrinking cement paste and the non-shrinking aggregates. In recent years, different models that consider the restraining effect of aggregates, i.e. Series model and Hobbs' model, have been proposed to predict the autogenous shrinkage of mortar and concrete. However, in these models both aggregate particles and cement paste matrix are considered as elastic materials. In fact, cement paste is not ideally elastic. Creep also plays an important role in autogenous shrinkage of mortar and concrete. In this paper an extended Pickett model, which takes the effect of creep into consideration, is proposed. The autogenous shrinkage of CEM I and CEM III/B cement mortar and concrete is simulated by using this model and compared with the experimental results to evaluate the accuracy of the predictions. The results show that the extended Pickett model can well predict the autogenous shrinkage of mortar and concrete.